Studi Kasus: Dinamika Psikologis pada Ibu Hamil dengan Other Specified Anxiety Disorder - Amirafatin Salsabila; Andik Matulessy (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Pregnancy is a period that may increase women’s vulnerability to psychological problems, particularly anxiety, which can affect the well-being of pregnant women. This study aims to describe the psychological dynamics, assessment process, and diagnosis of an early adult pregnant woman who experienced symptoms of anxiety. Using a case study approach supported by psychological assessments, including DASS, 16PF, SSCT, Wartegg, DAP, Baum, HTP, and SPM, the findings show that excessive anxiety was related to concerns about the maternal role, fetal health, family conditions, and the child’s future. Based on the integration of assessment results and DSM-5 criteria, the subject was diagnosed with Other Specified Anxiety Disorder with generalized anxiety features that had not yet met the duration criterion. These findings highlight the importance of comprehensive psychological assessment in supporting early identification and appropriate intervention planning.